«Eurocommunism» and the split of the Communist movement in Spain - Evgeny Astakhov (Ибероамериканские тетради)
In the period post Franco were created more favorable conditions for left parties, ﬁrst of all for Communist party. However, «eurocommunists» leadership of the Communist party of Spain (KPI) led her to a deep crisis. The creation in January 1984 of the new Communist party of the people of Spain (PCPE), despite the difﬁculties of institutional development, the complicated ﬁnancial situation, lack of personnel, became a signiﬁcant factor in the national political ﬁeld. After many years of political and ideological disarmament of the left forces in Spain appeared a party, acting with genuine class positions. At the same time, PCPE played the role of catalyst of processes oriented to shift to the left axis of the political life of the country. However, the current situation in the Spanish communist movement, the whole objective situation in Spain dictated the need for the uniﬁcation of the communists. That goal was answered by the creation of a left electoral coalition «United left».